Examining movement variability in the basketball free-throw action at different skill levels - Button, C.; MacLeod, M.; Sanders, R.; Coleman, S. (Research Quarterly for Exercise and Sport, 2003)
The analysis of variability both within and between performers can reveal important information about how athletes satisfy situational constraints. Transitory changes in the basketball free-throw shot were examined across different stages in skill development. Six female basketball players were selected, representing a range of playing expertise (pretest: 0-90% baskets scored). Each participant was video recorded performing 30 shots. Contrary to predictions, there was not a clear pattern of a reduction in trajectory variability with increasing skill level. However, improvements in skill level were associated with an increasing amount of intertrial movement consistency from the elbow and wrist joints. It is suggested that the angular motions of the elbow and wrist joints were compensated for each other toward the end of each throw to adapt to subtle changes in release parameters of the ball.